The complete mitochondrial genome sequence of Kichulchoia multifasciata (Teleostei, Cypriniformes, Cobitidae). (2nd January 2017) - Park, Chang Eon; Park, Gun-Seok; Kim, Min-Chul; Kim, Kgu-Hwan; Park, Hee Cheon; Shin, Jae-Ho
Abstract: The Kichulchoia multifasciata (Teleostei, Cypriniformes, Cobitidae) is one of the loaches and is endemic to Korea. The complete mitochondrial genome sequence consisted of 16 569 base pairs (bp) encoding 13 protein-coding genes (PCGs), 2 ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs) and 2 non-coding region. The overall base composition of K. multifasciata was G + C: 42.5% and A + T: 57.5%, apparently with a slight AT bias. Phylogenetic analysis showed that K. multifasciata was closely related to Koreocobitis rotundicaudata .